Unraveling the propagation dynamics of radially polarized anomalous vortex beams in turbulent maritime atmospheres - Hassan Al-Ahsab; Mingjian Cheng; Yuancong Cao; ShuaiLing Wang; Xiang Yi; Lixin Guo (Results in Physics)
Based on the unified theory of coherence-polarization, we utilize the extended Huygens-Fresnel principle to derive analytical expressions for the average intensity distribution of a radially polarized anomalous vortex beam (RPAVB) propagating through non-Kolmogorov maritime atmospheric turbulence. The hollow structure of the RPAVB can be sustained over long distances by manipulating the self-focusing point position, which depends on the initial beam parameters. This manipulation effectively mitigates the effect of maritime atmospheric turbulence. Additionally, the RPAVB undergoes a transition into a Gaussian form at significant distances, which can be intentionally slowed down by increasing the beam order, topological charge, beam width, or reducing the turbulent strength.